Perjanjian Asuransi Pertanian Pada Program Ketahanan Pangan Oleh Pemerintah - Vandawati, Zahry; Dermawan, Rizki; Sabrie, Hilda (Jurnal Hukum & Pembangunan, 2019)
In an effort to achieve food security, the government seeks to protect agricultural products by means of agricultural insurance programs. The insurance company is liable to compensate farmers in case of losses incurred by risks such as floods, droughts and plant disturbing organisms. Legal protection for farmers is given in accordance with the rights of peasants mandated by the Law. This research uses a type of normative legal research to find the rule of law, legal principles, and relevant legal doctrines and conduct a study of legal concepts. The approach method used in this research is the legislative approach and conceptual approach to examine the accountability of insurance companies and legal protection for farmers against agricultural insurance agreement on food security programs by the government.